ONOMASIOLOGICAL APPROACH TO THE LEXICAL SYSTEM (Scientific journal of the Fergana State University, 2024)
The article examines the opinions of linguists regarding the scientific views on naming things. Although all the words in the language have meaning, it is explained that they differ from each other according to the most general feature of the meaning. In onomasiology, the basics of naming things and events or concepts are studied; etymology determines the origin of words; In phraseology, there is a debate about stable combinations-phrases in the vocabulary of the language.